Oligomerization and Auto-methylation of the Human Lysine Methyltransferase SETD6. Issue 21 (19th October 2018) - Weil, Lital Estrella; Shmidov, Yulia; Kublanovsky, Margarita; Morgenstern, David; Feldman, Michal; Bitton, Ronit; Levy, Dan
Abstract: Signaling via lysine methylation by protein lysine methyltransferases (PKMTs), has been linked to diverse biological and disease processes. The mono-methyltransferase SETD6 (SET-domain-containing protein 6) is a member of the PKMT family and was previously shown to regulate essential cellular processes such as the NF-κB, WNT and the oxidative stress pathways. However, on the biochemical level, little is known about the enzymatic mode of action of SETD6. Here we provide evidence that SETD6 forms high-molecular-weight structures. Specifically, we demonstrate that SETD6 monomeric, dimeric and trimeric forms are stabilized by the methyl donor, S -adenosyl-l -methionine. We then show that SETD6 has auto-methylation activity at K39 and K179, which serves as the major auto-methylation sites with a moderate auto-methylation activity toward K372. A point mutation at K179 but not at K39 and K372, located at the SET domain of SETD6, impaired SETD6 ability to form a trimer, strongly implying a link between the auto-methylation and the oligomerization state. Finally, by radioactive in vitro methylation experiments and biochemical kinetics analysis, we show that the auto-methylation at K39 and K179 increases the catalytic rate of SETD6. Collectively, our data support a model by which SETD6 auto-methylation and self-interaction positively regulate its enzymatic activity in vitro and may suggest that other PKMTs are regulated in the same manner. Graphical Abstract: Highlights: SETD6 forms monomers, dimers and trimers as well as higher-molecular-weight structures. SETD6 monomeric, dimeric and trimeric forms are stabilized by the methyl donor, S -adenosyl-l -methionine. K39 and K179 serve as the major auto-methylation sites of SETD6. SETD6 auto-methylation at K39 and K179 increases SETD6 enzymatic activity.